An Improved HRPE-Based Transcriptional Output Reporter to Detect Hypoxia and Anoxia in Plant Tissue - Gabriele Panicucci; Sergio Iacopino; Elisa De Meo; Pierdomenico Perata; Daan A. Weits (Biosensors, 2020)
Oxygen levels in plant tissues may vary, depending on metabolism, diffusion barriers, and environmental availability. Current techniques to assess the oxic status of plant cells rely primarily on invasive microoptodes or Clark-type electrodes, which are not optimally suited for experiments that require high spatial and temporal resolution. In this case, a genetically encoded oxygen biosensor is required instead. This article reports the design, test, and optimization of a hypoxia-signaling reporter, based on five-time repeated hypoxia-responsive promoter elements (HRPE) driving the expression of different reporter proteins. Specifically, this study aimed to improve its performance as a reporter of hypoxic conditions by testing the effect of different untranslated regions (UTRs) at the 5′ end of the reporter coding sequence. Next, we characterized an optimized version of the HRPE promoter (HRPE-Ω) in terms of hypoxia sensitivity and time responsiveness. We also observed that severe oxygen deficiency counteracted the reporter activity due to inhibition of GFP maturation, which requires molecular oxygen. To overcome this limitation, we therefore employed an oxygen-independent UnaG fluorescent protein-coupled to an O2-dependent mCherry fluorophore under the control of the optimized HRPE-Ω promoter. Remarkably, this sensor, provided a different mCherry/UnaG ratiometric output depending on the externally imposed oxygen concentration, providing a solution to distinguish between different degrees of tissue hypoxia. Moreover, a ubiquitously expressed UnaG-mCherry fusion could be used to image oxygen concentrations directly, albeit at a narrow range. The luminescent and fluorescent hypoxia-reporters described here can readily be used to conduct studies that involve anaerobiosis in plants.